2019
DOI: 10.1002/jsid.783
|View full text |Cite
|
Sign up to set email alerts
|

Large‐area spatial atomic layer deposition of amorphous oxide semiconductors at atmospheric pressure

Abstract: Indium gallium zinc oxide (IGZO) is deposited using plasma‐enhanced spatial atomic layer deposition (sALD) on substrates as large as 32 × 35 cm2. Excellent uniformity and thickness control leads to high‐performing and stable coplanar top‐gate self‐aligned (SA) thin‐film transistors (TFTs). The integration of a sALD‐deposited aluminum oxide buffer layer into the TFT stack further improves uniformity and stability. The results demonstrate the viability of atmospheric sALD as a novel deposition technique for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…[16,17] This makes sALD well-suited for highly precise, high throughput, and in-line material processing over large areas, e.g., roll-to-roll and sheet-to-sheet sALD. [18][19][20] ALD relies extensively on the underpinning reactive chemistry of precursors. As such the development of new and more reactive precursors is an essential method of improving GPC and overall deposition rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] This makes sALD well-suited for highly precise, high throughput, and in-line material processing over large areas, e.g., roll-to-roll and sheet-to-sheet sALD. [18][19][20] ALD relies extensively on the underpinning reactive chemistry of precursors. As such the development of new and more reactive precursors is an essential method of improving GPC and overall deposition rate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16,17 ] This makes sALD well‐suited for highly precise, high throughput, and in‐line material processing over large areas, e.g., roll‐to‐roll and sheet‐to‐sheet sALD. [ 18–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Ga-ions could hinder the formation of oxygen vacancies, suppressing the generation of free carriers and thus a decrease in field effect mobility with increased Ga-content was observed. 43 Later, Katsouras et al 48 demonstrated the uniform deposition of IGZO on large substrates via the integration of an s-ALD-deposited Al 2 O 3 buffer layer into the TFT stack. The final products showed low off-currents and field effect mobility of 9 cm 2 V −1 s −1 .…”
Section: Recent Applications Of Atmospheric Atomic Layer Depositionmentioning
confidence: 99%
“…To overcome these tradeoffs, atomic layer deposition (ALD) is a powerful vapor-phase deposition process that affords unparalleled control of film thickness and conformality, owing to the self-limiting nature of surface reactions. , The previous literature has shown that by tuning the processing conditions, ALD precursors can infiltrate through ultrafine pores to provide uniform coatings with ultra-high aspect ratios (>50,000:1) and can conformally coat complex topologies with re-entrant texture, without gradients in film thickness or composition. Furthermore, many ALD processes can be performed at relatively low temperatures (typically <250 °C), which is compatible with a wide range of substrate materials including flexible polymers or biological/organic templates. ,, More recently, advances in spatial ALD processes and instrumentation have increased the throughput of ALD by several orders of magnitude and are compatible with roll-to-roll manufacturing. These attributes of ALD make it an ideal method to integrate with additive manufacturing processes such as 3D printing as ALD films can conformally modify complex object surfaces with sub-nanometer precision in composition, thickness, and structure. However, the integration of ALD with additive manufacturing remains in its infancy. , …”
Section: Introductionmentioning
confidence: 99%